U lancu mijenjajućih paradigmi bosanstva / Within the Chain of Changing Bosnianhood Paradigms - Mahmutćehajić, Rusmir (Pregled: časopis za društvena pitanja / Periodical for social issues, 2022)
The book Discourse on Bosnianhood (Sarajevo: Faculty of Political Sciences, 2020), by Senadin Lavić, is the reason behind the Fifth Roundtable Discussion Sarajevo in Contemporary Interpretations of European History, within the Culture and Politics of the Eighth International Conference Sarajevo and the World, held in Sarajevo on 16 May 2022.